Kemampuan Berpikir Kreatif dan Kemandirian Belajar Matematika Siswa Melalui Model Problem Based Learning - Rika Silviani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to describe the ability of creative thinking and independent learning of students during the learning process PBL models and find out the improvement of students' creative thinking skills after using PBL models of class VIII students of SMP Negeri 6 Banda Aceh. This research uses mixed methods (mixed methods) with a concurrent embedded strategy. The sample was chosen by random sampling, namely students of class VIII-3, amounting to 28 people from all students of class VIII. The instrument in this study was a daily description test, observation and questionnaire. This instrument is used to obtain data to increase students' creative thinking abilities after using the PBL model in the form of a pre-test and a post-test, as well as an instrument used to describe the independence of student learning during the PBL model learning process. Data analysis on the results of the daily description test and observation using the rubric of the assessment of the ability to think creatively with qualitative descriptive methods. The results of the pretest-posttest were analyzed by statistical tests, and the results of the learning independence questionnaire were analyzed using a Likert scale and percentage. The results showed that students were creative in solving problems related to comparisons during the PBL model learning process. Conclusion, there is an increase in students' creative thinking skills after using PBL model learning. The results also showed students had independence of learning during the PBL model learning process. Keywords: Creative Thinking Ability, Learning Independence, Problem Based Learning (PBL) Model.